A sequential injection system for the in-line digestion and colorimetric determination of phosphorus in milk - Lima, M.J. Reis (2011)
A sequential injection analysis (SIA) system involving in-line digestion for the determination of total phosphorus in milk is presented. The developed manifold consists mainly of 2 phases: conversion of all forms of phosphorus into orthophosphates by hydrolysis and oxidation catalyzed by UV radiation (necessary for the efficient oxidation of organic phosphates) and spectrophotometric determination of the phosphomolybdenum blue formed. The proposed method was applied to several cow milk samples and the results were in good agreement with those provided by the reference method, with a maximum relative deviation of 5.2%. The detection limit of the method was around 2 mg P/L with a sampling rate of approximately 17 h−1.